ANALISIS PEMASARAN GARAM KUSAMBA DI KECAMATAN DAWAN, KABUPATEN KLUNGKUNG - Sega Neli Riyanti, Dewa Ayu; Satriawan, I Ketut; Bayu Sadyasmara, Cokorda Anom (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): JuniDO - 10.24843/JRMA.2019.v07.i02.p01, 2019)
This research was carried out in Kusamba Village, Dawan District, Klungkung Regency. This study aims to find out to identify the salt kusamba marketing channel with the structure, conduct, performance (SCP) approach and analyze the marketing efficiency of kusamba salt. The data collected was analyzed with qualitative and quantitative methods. Qualitative methods are used to analyze marketing channels, structure, and market behavior, while quantitative methods are used to analyze market performance. Based on the results of the study, it can be concluded that the salt marketing process is through 4 (four) marketing channels. The market structure that occurs in the marketing of kusamba salt is oligopsonia. Market conduct occurs when the practice of pricing is still dominated by intermediary traders. Market performance shows that the highest total marketing margin is found in marketing channel 3 and the highest farmer share is found in marketing channels 1. The analysis of salt marketing efficiency based on farmer 's share states that the marketing channel 1 is the most efficient and based on the total marketing costs of marketing channel 3 is the most efficient because the value of Marketing Efficiency (EP) is 44,44% or ? 50%. Keywords : Kusamba sea  salt, structure, conduct, performance, and  marketing efficiency